2010
DOI: 10.1590/s0103-84782010005000181
|View full text |Cite
|
Sign up to set email alerts
|

Garlic extract improves budbreak of the 'Niagara Rosada' grapevines on sub-tropical regions

Abstract: In the regions with mild winters, usually the chilling requirements for bud dormancy release of grapevines are not fulfilled, and only the highly toxic products

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 10 publications
0
4
0
3
Order By: Relevance
“…Rady and Seif El-Yazal (2014) identified in their study that the use of garlic extract in order to anticipate sprouted buds increased the yield in apple trees. In addition to these authors, Kubota et al (2000) and Botelho et al (2010) also found that garlic extract had a great potential in breaking dormancy in grapevines.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Rady and Seif El-Yazal (2014) identified in their study that the use of garlic extract in order to anticipate sprouted buds increased the yield in apple trees. In addition to these authors, Kubota et al (2000) and Botelho et al (2010) also found that garlic extract had a great potential in breaking dormancy in grapevines.…”
Section: Resultsmentioning
confidence: 93%
“…Botelho et al (2010) included the garlic extract as an alternative substance to be employed, which provided good results. The aim of this study was to evaluate the effect of different doses of natural garlic extract (EAN) and Bioalho® added or not to mineral oil (OM), in overcoming the dormancy of buds of the cultivar 'Isabel Precoce' in the edaphoclimatic conditions of the region of Lavras -MG.…”
Section: Introductionmentioning
confidence: 99%
“…However, the Environment Protection Agency has classified this product as highly toxic, and the search for other products is required. Therefore, aiming to find natural products to replace the cyanamide use for dormancy bud breaking, the study of the effect of other products is required, as for instance the garlic extract that has been presenting positive results according to Botelho et al (2010).…”
Section: Grapes Cropmentioning
confidence: 99%
“…Nevertheless, grapevine culture shows several problems, mainly with the pests and diseases Botelho et al 2010). Conventional genetic breeding is used to solve several problems but has some limitations.…”
Section: Introductionmentioning
confidence: 99%